Page 53 - ISCI’2017
P. 53

e i X  i j +u  + e λ u − 1 X  i j +u − 1  + ...+ e λ 1 X  i + j  1  + e λ 0 X  i j  = 0
                                               i
                                                                          i
                                                                i
                  The last equality holds for any j and i. Will sum by all i = 0…n – 1:
                                   N
                                    −
                                   ∑ 1 ( X  i j +u  + e λ u − 1 X  i j +u − 1  + ...+ e λ X  i + j  1  + e λ 0 X  i j ) 0 .
                                                                                  =
                                       e
                                                i
                                        i
                                                                           i
                                                                 i
                                                                   1
                                    = i  0
                  Change the order of summation, will get out the coefficients of the polynomial Λ(x) to a sign
            of summation, we will get:
                              N − 1           N − 1               N − 1         N − 1
                                e  X  i  + λ  ⋅  e  X  i  + ...+ λ ⋅  e  X  i  + λ  ⋅  e  X  i  =  0.
                              ∑ i   j +u  u − 1 ∑ i  j +u − 1  1 ∑ i     + j  1  0 ∑ i  j
                              = i  0           = i  0             = i  0         = i  0
                  The value  of each  summand  in the  last expression corresponds to a multiplication of the
            coefficients of the polynomial Λ(x) to the corresponding syndromes in the expression (11), so we can

            write
                                       sj+u + λu-1 ∙ sj+u-1 + … + λ1 ∙ sj+1 + λ0 ∙ sj = 0.

                  We rewrite the expression for each j = 0…u, we obtain a system of linear equations:

                                         su + λu-1 ∙ su-1 + … + λ1 ∙ s1 + λ0 ∙ s0 = 0,
                                        su+1 + λu-1 ∙ su + … + λ1 ∙ s2 + λ0 ∙ s1 = 0,                                         (14)

                                                           …

                                       s2∙u + λu-1 ∙ s2∙u-1 + … + λ1 ∙ su+1 + λ0 ∙ su = 0.
                  System from u linear equations (14) withe u variables (unknowns) can be solve, the complexity

            of its solution increases polynomial from the number of variables (unknowns) [38-40]. For example,

                                                                                       3
            the solution for systems (14) by the Gaussian elimination will need to execute u  arithmetic operations
            (additions and multiplications over the elements of the field GF(q )).
                                                                           m
                  Solution of the system (14) gives the values of the error locator polynomial coefficients (13).
                                                                                             m
            Radicals of the polynomial (13) are the locators, which are elements of the field GF(q ), which clearly
            indicate the location of the non-zero elements of the error vector e. Consequently, the radicals of the

            equation (13) is necessary to find for fault isolation.
                  The  most simple procedure  of the radicals search  Λ(x)  consists  in a substitution  into a

            polynomial all n elements Xj ∈ GF(q ) and selecting those elements that become zero Λ(x). In the
                                                m
            literature, this technique is called the procedure Chenya [38-40]. Based on Horner scheme will rewrite
            the polynomial Λ(x) as

                                                                                    x
                                                                            x
                                                                                              x
                     Λ (x ) = x u  + λ − 1 x u − 1  + λ − 2 x u − 1 ... λ ++  1 x  λ =  (...(( + λ u − 1 ) +  λ u − 2 ) + ... λ+  1 ) + λ .
                                                                    x
                                                            0
                                                                                                   0
                                  u
                                           u
                  For a calculation of a volume of the polynomial Λ(x) in this form, will need no more u – 1
                                                                                                     m
            arithmetic operations (additions and  multiplications  over the  elements of the  field  GF(q )), i.e.
            complexity of this decoding step does not exceed n(u – 1) arithmetic operations.
                                                                                                          53
   48   49   50   51   52   53   54   55   56   57   58